2021
DOI: 10.5603/cj.a2020.0130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of angiotensin converting enzyme inhibitor versus angiotensin ii type i receptor blocker in acute myocardial infarction with non-obstructive coronary arteries; from the Korea Acute Myocardial Infarction Registry — National Institute of Health

Abstract: Background: Selecting angiotensin converting enzyme inhibitor (ACEI) or angiotensin II type I receptor blocker (ARB) in patients diagnosed as acute myocardial infarction (AMI) with non-obstructive coronary arteries (MINOCA) is not established. The purpose of this study is to compare the clinical effect of ACEI vs. ARB in MINOCA patients. Methods and results: A total of 273 patients between November 2011 to June 2015, diagnosed with MINOCA who were registered in the Korea AMI Registry-National Institute of Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Conforme os achados, 87,5% (n=7) dos estudos abordaram estratégias terapêuticas farmacológicas, (14)(15)(16)(17)(19)(20)(21) apenas um estudo abordou estratégia de diagnóstico de causa adjacente (18) e não houve estudos que abordassem estratégias não medicamentosas para pacientes após diagnóstico de MINOCA.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Conforme os achados, 87,5% (n=7) dos estudos abordaram estratégias terapêuticas farmacológicas, (14)(15)(16)(17)(19)(20)(21) apenas um estudo abordou estratégia de diagnóstico de causa adjacente (18) e não houve estudos que abordassem estratégias não medicamentosas para pacientes após diagnóstico de MINOCA.…”
Section: Resultsunclassified
“…Por outro lado, o uso de inibidores do sistema renina-angiotensina-aldosterona (SRAA) foi comprovado como benéfico em três estudos (37,5%), (15,19,21) um estudo obteve evidência de que os inibidores da enzima conversora de angiotensina (IECA) são a melhor opção em comparação aos bloqueadores do receptor da angiotensina II (BRA), por reduzir reincidência de infarto, salvo contraindicações. ( 19) Além disso, 62,5% (n=5) dos estudos selecionados fazem citação aos inibidores de SRAA como estratégia terapêutica favorável para MINOCA .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Regarding medical management of these patients, clinical registry based studies suggest MINOCA patients are often less likely to receive secondary preventive medications when compared to MICAD patients (7)(8)(9). However, studies have reported benefits of ACEI/ARB therapy (10)(11)(12)(13), statin therapy (11,14), and beta blocker (15) therapy in MINOCA. In particular, Lindahl et al (13) using data from the Swedish Web-system for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies (SWEDEHEART) registry of 9,136 MINOCA patients showed that 24% experienced a Major Adverse Coronary Events (MACE) during a mean follow-up period of 4.1 years.…”
Section: Introductionmentioning
confidence: 99%